Creativity of beauty philosophy in aesthetic work - النداف, فارس; اسماعيل, عفراء; سليمان , ميرنا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Between the beauty in the whole existence and the beauty in the art's philosophy reveals the the heart of the research. There is what is good, loved, praised, and there is what is ugly and rejected. Beauty suits the human nature like joy and it is known as the meaning of perfection, while ugliness is known as the meaning of lacking it. The concept of beauty is general and it can include beautiful forms and human actions. Therefore , acts of honesty and loyalty are described as good deeds. However, this research will focus on showing the beauty that the artist creats in his work, while he is seeking for the aesthetic ideal. He shows that the lack of beauty expressed in art becomes a real beauty. The value of art lies in creativity of various forms of beauty, seeking for perfection and beauty ideal.